Correlation between actual and pH corrected ionic calcium in critically ill pediatric patients - Dr.Kanak Ramnani; Dr. Sharja Phuljhele; Dr. Prachi BichpuriaD; Dr. Ankush Verma (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Many authors have tried to prove a causal relationship between hypocalcemia and increased mortality in ICUs. For many years correction of ionic calcium for albumin level and magnesium levels has been done. In vivo the importance of calculated ionic calcium for changes in pH has not been very well studied.Objective: The objective of our study is to find out if ionic calcium values (iCa) need to be corrected and calculated for in vivo acid base imbalances in ICU settings.Methods: The study was a time bound prospective study done from November 2016 to May 2017 in PICU of Dr. B.R.A.M. Hospital, Raipur, Chhattisgarh. The ABGs and ionic calcium of all the critically ill children were collected according to inclusion & exclusion criteria. The iCalevels of the ABG machine was considered as the actual iCa value and the iCavalues were corrected for pH of 7.4 using the standard formula. The differences in ionic calcium levels and corresponding calculated ionic calcium levels were statistically analysed for significance using “paired t test”.Results: A total of 239 reports were studied, 80 records were acidotic, 78 exhibited normal pH and 81 had alkalosis. The difference between ionic calcium (iCa) and corrected ionic calcium (iCac) values were found significant [p=0.022] for moderate and severe acidosis. However, normal pH group [p=0.05186] and alkalosis group [p=0.0729] had insignificant differences.Conclusion: iCa, especially the actual iCa from the ABG reports should be considered for the treatment purposes specially in the case of acute acidosis.